Efeito de fatores históricos e ambientais sobre a composição e diversidade de assembleias de lagartos no sudoeste da Amazônia brasileira - Peixoto, Gabriela Marques (Instituto Nacional de Pesquisas da Amazônia - INPA, 2019)
Ecological studies with standardized sampling conducted on a large scale can provide an understanding of patterns and processes hitherto unknown in the structuring of megadiverse assemblages such as those from the Neotropics. In this thesis we present an analysis based on multiple sampling sites installed along a transect of approximately 1,000 km, in the Purus- Madeira interfluve and on the banks of the Upper Madeira River, in order to understand the distribution of the lizard assemblages of this region. In the first chapter we characterized the composition and abundance of the lizard assemblage in 10 sampling modules along the BR- 319 highway. We counted 25 taxa belonging to eight families, distributed heterogeneously along the interfluve. We also we emphasize the importance of faunal surveys for future conservation measures of the species of lizards of interfluvial regions in face of the increasing anthropic impact in Amazonia. In the second chapter we evaluated how the environmental heterogeneity, mainly associated with the Open and Dense Ombrophilous Forests of the region of the Purus-Madeira interfluve forms the lizard assemblages. For this, we quantified the assemblies through taxonomic and functional measures in fourteen sampling modules. We observed that environmental factors such as soil, vegetation and rainfall vary in biogeographic scale along the interfluve and influence the pattern of occurrence of species and functional richness of the assemblages. Thus, we detected a large-scale species substitution pattern shaped by the influence of environmental filters. In the third chapter we investigated, at different scales, the influence of historical and ecological factors in the structure of lizard assemblages in the region of the upper Madeira River. For this, 83 plots were sampled along the east and west banks of the river. At the regional level, the upper Madeira River acts as a biogeographic barrier to 29.6% of the species. In contrast, the performance of environmental filters explains the structure of the assemblages at a local scale. This study, which pioneered such a wide geographic scale in the ecology of Amazonian lizards, suggests that historical and ecological factors have hierarchical effects in determining the spatial structuring of assemblages. Such as the present investigation, future research addressing different scales according to standardized sampling methods promises to elucidate processes and patterns related to the heterogeneous spatial distribution of Amazonian biodiversity.
Keywords: BR-319; Heterogeneidade ambiental; Inambari; Rios como barreira